LEMPUNG CENGAR TERAKTIVASI ASAM SULFAT SEBAGAI HASIL SAMPING PRODUKSI KOAGULAN: KARAKTERISASI - Fiola Reviola; Muhdarina '; Nurhayati ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Cengar Natural clay was calcined at 700°C for 3 hours and the clay was extracted usingsulfuric acid with various of concentration (0.2, 0.4 and 0.6 moles) at 30 o C for 1 hour for liquid coagulant synthesis. The by product of liquid coagulant production was the sulfuric acid activated Cengar clay which have been used in this study. The sulfuric acid activated Cengar clay solids was heated at 230°C for 5 hours. The activated Cengar clay were characterized to determine the mineral types and ratio Si/Al. Characterization by X-ray diffraction (XRD) has shown a mineral of bassanite in clay at every moles of sulfuric acid, where as the types of clay mineral that only calcined at 700oC for 3 hours (LC700) were kaolinite, muscovite, monmorilonite, calcite and quartz. Ratio Si/Al in each of the sulfuric acid activated clays LC700-0,2, LC700-0,4 and LC700-0,6 were 7,76, 10,75 and 23,76, while non activated clay LC700 was 6,08. It is concluded that the activated clay was potential to be used as an adsorbent.